Medical prospects of cryptosporidiosis in vivo control using biofabricated nanoparticles loaded with Cinnamomum camphora extracts by Ulva fasciata - Nesreen Allam Tantawy Allam; Ragaa Abd El-Fatah Hamouda; Doaa Sedky; Mahinour Ezzeldin Abdelsalam; Mona Ebrahim Hussien Abd El-Gawad; Noha Mahmoud Fahmy Hassan; Dina Aboelsoued; Amal M. Abou Elmaaty; Muhammad A. Ibrahim; Hanan Anwar Aly Taie; Ashraf Samir Hakim; Hassan Mohamed Desouky; et al. (Veterinary World, 2024)
Background and Aim: Global efforts are continuing to develop preparations against cryptosporidiosis. This study aimed to investigate the efficacy of biosynthesized Ulva fasciata loading Cinnamomum camphora oil extract on new zinc oxide nanoparticles (ZnONPs shorten to ZnNPs) and silver nanoparticles (AgNPs) as alternative treatments for Cryptosporidium parvum experimental infection in rats.